2019
DOI: 10.1021/acs.analchem.9b04290
|View full text |Cite
|
Sign up to set email alerts
|

Biocatalytically Initiated Precipitation Atom Transfer Radical Polymerization (ATRP) as a Quantitative Method for Hemoglobin Detection in Biological Fluids

Abstract: The hemoglobin content of blood is an important health indicator, and the presence of microscopic amounts of hemoglobin in places where it normally does not occur, e.g. in blood plasma or in urine, is a sign of diseases such as hemolytic anemia or urinary tract infections. Thus, methods to detect and quantify hemoglobin are important for clinical laboratories, blood banks, and for point-of-care diagnostics. The precipitation polymerization of N-isopropylacrylamide by hemoglobin-catalyzed atom transfer radical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 62 publications
(98 reference statements)
0
22
0
Order By: Relevance
“…ATRPase is particularly suited for sensing applications because ATRPase acts on alkyl bromides (ATRP initiator) to generate radicals, which can avoid possible interference from easily produced, unsourced radicals. This distinct feature of ATRPase was recently exploited by the Bruns group for sensing hemoglobin and hemozoin (a marker of the malaria parasite) [40d,f,g] . Both hemoglobin and hemozoin were able to catalyze the precipitation ATRP of NIPAM, and quantitative detection was made possible through the solution turbidity (Figure 10).…”
Section: Applicationsmentioning
confidence: 99%
“…ATRPase is particularly suited for sensing applications because ATRPase acts on alkyl bromides (ATRP initiator) to generate radicals, which can avoid possible interference from easily produced, unsourced radicals. This distinct feature of ATRPase was recently exploited by the Bruns group for sensing hemoglobin and hemozoin (a marker of the malaria parasite) [40d,f,g] . Both hemoglobin and hemozoin were able to catalyze the precipitation ATRP of NIPAM, and quantitative detection was made possible through the solution turbidity (Figure 10).…”
Section: Applicationsmentioning
confidence: 99%
“…Given that hemoglobin itself can catalyze ATRP, Bruns and coworkers also demonstrated the use of hemoglobin-catalyzed precipitation polymerization to quantify the amount of hemoglobin in biological fluids. 59 In this method, the polymerization conditions were the same as the hemozoin-catalyzed ATRP 56 except that sample preparation method and buffer pH were slightly different. The dose-response curve between logarithmic hemoglobin concentration and the rate of turbidity increase showed that the rate of turbidity increase was positively correlated with the concentration of hemoglobin although the rate reached a plateau at high concentration.…”
Section: Biocatalytic Atrpmentioning
confidence: 99%
“…The dose-response curve between logarithmic hemoglobin concentration and the rate of turbidity increase showed that the rate of turbidity increase was positively correlated with the concentration of hemoglobin although the rate reached a plateau at high concentration. 59 According to authors, the plateau could appear likely because hemoglobin precipitated with PNIPAAm as polymerization proceeded. At low hemoglobin concentrations, the detection limit was 100 nM in buffer solution.…”
Section: Biocatalytic Atrpmentioning
confidence: 99%
See 1 more Smart Citation
“…Hemoglobin can also be detected by the assay in a sensitive way. 29 Hemozoin is a product of hemoglobin digestion by Plasmodium sp. parasites.…”
Section: Introductionmentioning
confidence: 99%